Pelatihan Penyusunan Bussines Plan Untuk Menciptakan New Entrepreneur Mahasiswa Pendidikan Ekonomi Fkip Universitas Jambi - Sri Dwijayanti, Novia; Rosmiati, Rosmiati; Sari, Nurmala; Putra, Iwan; Nasori, Ahmad (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2023)
This article results from Community Service activities, which discuss training in preparing business plans to create new entrepreneurs for economics education students at FKIP Jambi University. This study aims to provide training to students in making business plans correctly. It is hoped that training participants can prepare things that must be designed as new entrepreneurs so that they can anticipate as early as possible if undesirable things happen in their business journey. Activities are carried out in a participatory form using best practices for student entrepreneurship. The method for implementing this service adopts Deming's concept: Plan-Do-Check-Act (PDCA). After carrying out training by utilizing student potential, the results obtained were that students could create a draft blueprint from the effects of the activity in the form of students' understanding of preparing a media canvas business plan.